2017
DOI: 10.1016/j.ecolecon.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Neoclassical Trojan Horse of Steady-State Economics

Abstract: A B S T R A C TThe vision of a steady-state economy elaborated by Herman Daly describes an economy that uses materials and energy within the regenerative and assimilative limits of the planet's ecosystems. Sustainable scale, just distribution, and efficient allocation are its constitutive theoretical goals. This paper is a critique of the theoretical foundations of steady-state economics. It argues that steady-state economics consists in an attempt to squeeze neoclassical economics into a biophysical and ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…Human wellbeing is closely related to environmental quality [4]. Currently, human beings have transitioned from an 'empty world' with relatively rich natural capital to a 'full world' that falls under the restrictions of the ecological environment due to the deterioration of the ecological environment and depletion of natural resources [5,6]. In a 'full world', scarce natural capital has become the limiting factor of welfare promotion [7], Land 2021, 10, 12 2 of 17 and ecological welfare is approaching ecosystem limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Human wellbeing is closely related to environmental quality [4]. Currently, human beings have transitioned from an 'empty world' with relatively rich natural capital to a 'full world' that falls under the restrictions of the ecological environment due to the deterioration of the ecological environment and depletion of natural resources [5,6]. In a 'full world', scarce natural capital has become the limiting factor of welfare promotion [7], Land 2021, 10, 12 2 of 17 and ecological welfare is approaching ecosystem limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The free-market analogy used in this theory is effective from the perspective of increasing innovation in products, but at the same time, it must be noted that every innovation happening right now is not environmentally friendly. Studies have shown that there is a need to develop new products that are equally sustainable and provide more control toward the environmental variables that contribute to the degradation (Pirgmaier, 2017). This can be effectively done, as evident in previous studies, by employing strategic management controls.…”
Section: Literature Reviewmentioning
confidence: 96%
“…This is possible on practical grounds, but due to government strategies being implemented in the industrial sectors, this may not be possible in the protected time frames. This is because the economic models adopted by governmental institutions such as International Monetary Fund (IMF) have facilitated the public by providing multiple facilities in the market (Pirgmaier, 2017). This corresponds to the fact which is described according to the neoclassical theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a conspicuous dearth of keywords referencing inequality, power relations, the underlying cultural dimensions driving our ecological emergency; visions for a just and sustainable society; or the need for radical transformative change, despite a recent survey finding that 72% of ecological economists believe such radical change is necessary [56]. Many ecological economists conclude in dismay that the field is well on its way to converging with environmental economics [17,[57][58][59]. Research on our economy's biophysical foundations is essential, but also not useful if we cannot turn knowledge into action, which requires a deep understanding of the social sphere.…”
Section: Evolving Schools Of Thought Within Eementioning
confidence: 99%